PENERAPAN GREEN BANKING DI LINGKUNGAN BANK MUAMALAT INDONESIA - Ria, Desma; Fasa, Muhammad Iqbal; Suharto, Suharto; Fachri, Adib (Program Studi Perbankan Syariah FEBI UIN Ar-Raniry, 2023)
The increasing competition of business or industry makes the behavior of businessmen ignore the natural environment. This causes the emergence of seriousness from the corporate world to increasingly involve themselves in activities that can create a positive impact on social and natural environment. In addition to carry out its function as an intermediary institution, the banking industry is also currently required to be involved in suppressing environmental damage because it is considered necessary to adapt interdepedensially to the environment called Green Banking. This research aims to find out how to implement green banking in Bank Muamalat Indonesia environment. This research used qualitative method by impelementing descriptive analysis using secondary data. The results showed that there are two main green banking programs implemented by Bank Muamalat Indonesia, the distribution of environment friendly financing and environment friendly operational activities, respectively.